2017
DOI: 10.21101/cejph.a5098
|View full text |Cite
|
Sign up to set email alerts
|

National Time Trends in Bullying among Adolescents in the Czech Republic from 1994 to 2014.

Abstract: SUMMARYObjective: Bullying in school is a public health concern which continues to be a serious threat to physical and emotional health of children and adolescents. The purpose of this study is to examine trends in bullying behaviour among school-aged children in the Czech Republic.Methods: Data were obtained from cross-sectional self-report surveys in the years 1994-2014 as a part of the Health Behaviour in School-aged Children study (HBSC) from a representative sample of 11-, 13-, and 15-year olds.Results: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…Bullying was investigated using two questions adapted from the Olweus Bully/Victim Questionnaire [ 48 ] allowing to assess both victimization and perpetration . Those who reported that they have been bullied or have taken part in bullying another student(s) in the past couple of months at least once or twice were considered bullying victims and perpetrators, respectively, in subsequent analyses in line with a previous study using the Czech HBSC data [ 39 ]. The questions were preceded by the text explaining the term of bullying to respondents.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bullying was investigated using two questions adapted from the Olweus Bully/Victim Questionnaire [ 48 ] allowing to assess both victimization and perpetration . Those who reported that they have been bullied or have taken part in bullying another student(s) in the past couple of months at least once or twice were considered bullying victims and perpetrators, respectively, in subsequent analyses in line with a previous study using the Czech HBSC data [ 39 ]. The questions were preceded by the text explaining the term of bullying to respondents.…”
Section: Methodsmentioning
confidence: 99%
“…Data shows reducing trends of bullying among children and adolescents at the Czech schools in recent decades [ 39 ], yet bullying rates in Czechia are still around average in comparison to countries from Organization for Economic Co-operation and Development (OECD) [ 40 ]. The OECD’s report that children and students with low academic performance (including those with SDDSS) are more likely to become victims of bullying.…”
Section: Introductionmentioning
confidence: 99%
“…Bullying pada anak usia sekolah merupakan fenomena yang semakin meluas dan bertambah (Le et al, 2017). Menurut Bullying antar teman sebaya merupakan ancaman yang serius, karena memiliki dampak jangka panjang bagi korban maupun pelaku (Sarková, Sigmundová, & Kalman, 2017). Bagi korban, bullying dapat memberikan efek traumatis sepanjang kehidupan, korban akan menjadi anti sosial, korban menarik diri serta menjadi tidak peduli terhadap apa yang terjadi dilingkungan, apabila berlangsung dalam waktu yang lama anak akan menjadi depresi.…”
Section: Pembahasanunclassified